1970
DOI: 10.1172/jci106458
|View full text |Cite
|
Sign up to set email alerts
|

Effects of parathyroid hormone on plasma and urinary adenosine 3′,5′-monophosphate in man

Abstract: A B S T R A C T The effects of parathyroid hormone (PTH) on plasma and urinary adenosine 3',5'-monophosphate (cyclic AMP) levels were studied in normal subjects. Under basal conditions normal adults have plasma concentrations of cyclic AMP ranging from 10 to 25 nmoles/liter and excrete from 1.5 to 5 imoles of cyclic AMP per g of urinary creatinine. About one-half to two-thirds of the cyclic AMP excreted in the urine is derived from the plasma by glomerular filtration, and the remainder is produced by the kidne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
92
0
9

Year Published

1971
1971
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 258 publications
(108 citation statements)
references
References 21 publications
7
92
0
9
Order By: Relevance
“…Purification appeared to be unnecessary for assay of cyclic AMP and cyclic GMP in urine*. The infusion of calcium gluconate in a patient increased urinary excretion of cyclic GMP (Table 2) as reported previously (17).…”
Section: Assay Conditionssupporting
confidence: 56%
“…Purification appeared to be unnecessary for assay of cyclic AMP and cyclic GMP in urine*. The infusion of calcium gluconate in a patient increased urinary excretion of cyclic GMP (Table 2) as reported previously (17).…”
Section: Assay Conditionssupporting
confidence: 56%
“…PTH is one of the most potent acute phosphaturic factors inducing urinary phosphate excretion within 15 to 45 minutes after application (15,18). We and others have shown that PTH causes phosphate excretion at least in part by inducing the internalization of the NaPi-IIa phosphate cotransporter from the brush border membrane of proximal tubules in rats and mice (2,3,7,12,30,48).…”
Section: -mentioning
confidence: 99%
“…However, the relative contribution of these transporters to overall renal phosphate handling and the integration of several signals on the level of the proximal under these circumstances remains an open question. PTH application elicits a rapid phosphaturic response both in humans and rodents (15,18). In contrast to rodents, several lines of evidence suggest that NaPiIIa may not be the major type II phosphate transporters in human kidney.…”
Section: Napi-iic Expression Was Not Altered By Pth In Agreement Withmentioning
confidence: 99%
See 1 more Smart Citation
“…Fluctuations in the high basal ratios of milligrams phosphate/milligrams creatinine excretion [9] obscured a phosphaturic response to PTH, if indeed, this did occur (Table III). Thus, the increased excretion of 3',5'-AMP after PTH infusion can be interpreted as a demonstration of PTH responsiveness of the kidney in diis disease [5,9,23,30,41,44].…”
Section: 'Y-amp Excretionmentioning
confidence: 99%